Tapestry - Pallotta-Chiarolli, Maria (Milsons Point, New South Wales : Random House Australia, 1999)
The author explores the lives of five generations of her family as they move from the poor villages of Italy to life in the cities of Australia.
Keywords: Pallotta-Chiarolli, Maria, -- 1960-; Italians -- Australia -- Biography